2021
DOI: 10.1002/vms3.509
|View full text |Cite
|
Sign up to set email alerts
|

Infective mastitis due to bovine‐associated Streptococcus dysgalactiae contributes to clinical persistent presentation in a murine mastitis model

Abstract: Background Mastitis caused by Streptococcus dysgalactiae (GCS) is a major pathology of dairy cows. The mechanisms by which GCS intramammary infection is established and maintained involve not only bacterial adherence and invasion but also modulation of the cytokines and TLR immune response. Objectives The study aimed to evaluate characteristics of persistent infection of GCS collected from bovine mastitis milk in a murine mastitis model whose mammary structure is similar to that of dairy cows; dairy cow mastit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…However, the alterations in the expression of the above genes were significantly recovered by adding miR-155 inhibitor-loaded exosomes, which indicated that miR-155 might alleviate mastitis via the TLRs/NF-κB signaling pathway. The previous study has shown that the levels of TNF-α, IL-1β, and IL-10 were increased in Mastitis induced by LPS (37). We also found the same changes in the levels of TNF-α, IL-1β, and IL-10 in LPS-induced HC11 cells in our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, the alterations in the expression of the above genes were significantly recovered by adding miR-155 inhibitor-loaded exosomes, which indicated that miR-155 might alleviate mastitis via the TLRs/NF-κB signaling pathway. The previous study has shown that the levels of TNF-α, IL-1β, and IL-10 were increased in Mastitis induced by LPS (37). We also found the same changes in the levels of TNF-α, IL-1β, and IL-10 in LPS-induced HC11 cells in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, HLJ2019 was used to confirm the protective effect and demonstrate the positive benefits of rGAPDH in the lethal infection model. Previous research from the authors’ laboratory showed that HLJ2019 produces chronic infection symptoms in the mammary gland of the mice [ 30 ]. Recombinant GAPDH adjuvanted with Freund's adjuvant was synthesized and injected subcutaneously into mice.…”
Section: Discussionmentioning
confidence: 99%
“…Among microorganisms responsible for sheep mastitis, streptococci rank second in importance after staphylococci (Kumar et al 2013). Both S. uberis and S. agalactiae can induce chronic mastitis in cows (An et al 2021). Although, S. uberis is primarily an environmental pathogen, cases of transmission have been observed.…”
mentioning
confidence: 99%